Cumulative Embodied and Operational Emissions of Retrofit in Birmingham Zero Carbon House - Jankovic, Ljubomir; Christophers, John (Frontiers in Built Environment, 2022)
Birmingham Zero Carbon House was retrofitted and extended from an 1840 end of terrace house to an award-winning house with negative operational emissions, receiving a RIBA Award for Architecture in 2010. In addition to a super-insulated envelope, the house achieves its negative emissions status using a photovoltaic system, a solar thermal system and a wood burning stove. The house has bene extensively monitored since 2011, with circa 20 performance parameters recorded every minute of the day. Despite its negative operational emissions confirmed by the monitoring, this article for the first time introduces embodied emissions into the calculation of the overall carbon emissions performance. Taking into account embodied emissions from materials, construction process, maintenance and the end-of-life emissions due to deconstruction and disposal, taken over a sixty-year span, the analysis reveals that the sum of embodied and operational emissions reached zero in 2012. Taking a rigorous approach of quantifying embodied and operational emissions, the paper puts into perspective the scale of efforts that need to be deployed across the UK and beyond to reach net zero by 2050.